Conservative approach of a symptomatic carious immature permanent tooth using a tricalcium silicate cement (Biodentine): a case report - Cyril Villat; Brigitte Grosgogeat; Dominique Seux; Pierre Farge (Korean Academy of Conservative Dentistry, 2013)
The restorative management of deep carious lesions and the preservation of pulp vitality of immature teeth present real challenges for dental practitioners. New tricalcium silicate cements are of interest in the treatment of such cases. This case describes the immediate management and the follow-up of an extensive carious lesion on an immature second right mandibular premolar. Following anesthesia and rubber dam isolation, the carious lesion was removed and a partial pulpotomy was performed. After obtaining hemostasis, the exposed pulp was covered with a tricalcium silicate cement (Biodentine, Septodont) and a glass ionomer cement (Fuji IX extra, GC Corp.) restoration was placed over the tricalcium silicate cement. A review appointment was arranged after seven days, where the tooth was asymptomatic with the patient reporting no pain during the intervening period. At both 3 and 6 mon follow up, it was noted that the tooth was vital, with normal responses to thermal tests. Radiographic examination of the tooth indicated dentin-bridge formation in the pulp chamber and the continuous root formation. This case report demonstrates a fast tissue response both at the pulpal and root dentin level. The use of tricalcium silicate cement should be considered as a conservative intervention in the treatment of symptomatic immature teeth.